Controllable localization of carbon nanotubes on the holey edge of graphene: an efficient oxygen reduction electrocatalyst for Zn–air batteries. Issue 47 (18th October 2016) - Cheng, Zhihua; Fu, Qiang; Li, Changxia; Wang, Xiaopeng; Gao, Jian; Ye, Minghui; Zhao, Yang; Dong, Liujia; Luo, Hongxia; Qu, Liangti
Abstract : An efficient oxygen reduction reaction (ORR) catalyst based on a three dimensional holey graphene framework with precise localization of N-doped carbon nanotubes (N-CNTs) on the hole-edges of graphene is demonstrated. Abstract : The rational design and construction of carbon nanostructures, particularly those assembled from carbon nanotubes (CNTs) and graphene because of their superior synergistic advantages, are of significance for the development of metal-free electrocatalysts with low cost and high activity in energy conversion and storage fields. Herein, we report a highly efficient oxygen reduction reaction (ORR) catalyst based on a three dimensional nitrogen-doped CNTs–holey graphene framework (N-CNTs–HGF) formed by the in situ, precisely positioned growth of nitrogen-doped CNTs on the holey-edges of porous graphene sheets. Benefiting from the unique hierarchical structure of CNTs and graphene with the merits of fast charge and mass transport along the interfaces of holes, the resultant catalyst exhibits superior capability towards catalyzing oxygen reduction, which affords a positive onset potential of 1.08 V vs. RHE, small Tafel slope of 72 mV dec −1 and half-peak potential of 0.85 V vs. RHE. Furthermore, its potential practical application is also evidenced by simply integrating it into an all-solid-state Zn–air battery.